Impact of Government Intervene in Oligopoly Market Using Tawhidi String Relation Approach Case Study of Toll Road Operators in Indonesia - Cahyo Satrio Prakoso (BPJP - STEI, 2021)
This paper aims to investigate the government's intervention in an oligopoly market from an Islamic Economic point of view. The toll road industry in Indonesia is one of the best case studies of the impact of government intervention in pricing policy. Methodology/approach – Referring to some Islamic scholars concerning pricing policy, this paper using Tawhidi String Relations or TSR concept as a method to explain the variation tariff using the proposed variables. Findings – The result shows that Islamic economics does not prohibit government intervention in oligopoly markets as long as the pricing policy favors the public. In the case of the toll road industry in Indonesia, government intervention is needed to benefit the public and generate economic growth between cities. Practical implications – Pricing policy in the toll road industry in Indonesia should incorporate other variables such as development strategies of the cities in order to raise economic growth of the cities. Originality/value – The Tawhidi String Relations method could be applied to all aspects of life in the world. This TSR methodology can be the frame of mind of various scientific studies on how society achieves consensus to solve various problems by referring to Islamic teachings, in an effort to create benefits from the purpose of peace in the world. TSR becomes a frame of mind that explains how Divine Laws affect the scientific social order of the world, through a process of Interaction, Integration, and Evolution (IIE Process) (Choudhury, 2019)